Pengolahan Limbah Cair Pabrik Kelapa Sawit Dengan Metode Fitoremediasi Menggunakan Typha Latifolia - Purwanti, Purwanti; Elystia, Shinta; Sasmita, Aryo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Treatment of palm oil mill effluent still leaves a lot of challenges in terms of both technology and quality standards. Therefore, we need a wastewater treatment system that can provide optimal results in processing and controlling the environmental impact of waste that can be reduced. Phytoremediation is a method of alternative technologies need to be developed to address these challenges. This study aims to determined the pollutant removal efficiency parameters BOD in the palm oil mill effluent, study the influence of variations in plant density, waste content variation, and variation of the residence time of the wastewater treatment efficiency of phytoremediation method. Compare the results of treatment of palm oil mill effluent by phytoremediation method using Typha latifolia with effluent standards for palm oil mill based on the Keputusan Menteri Lingkungan Hidup Nomor 51 Tahun 1995. This research used reactor phytoremediation the size of 50cm x 36cm x 31cm, thickness 10cm soil media, media thickness 5cm sand and gravel media 5cm thick with research variables include plant density variations Typha latifolia (0,5g/cm2; 0,75g/cm2; dan 1g/cm2), variations in the levels of palm oil effluent (20%; 60%; dan 100%), and variation of the residence time ( 5 days and 9 days ). The results showed that the highest efficiency is on density variations in plant 1 g/cm2 , 20% waste concentration, and residence time of 9 days with BOD 97,33 %. Keywords: Levels of Waste, Palm Oil Mill Effluent, Phytoremediation, Plant Density, Typha latifolia.